2004
DOI: 10.1210/jc.2003-031811
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling Distinguishes Papillary Carcinoma from Benign Thyroid Nodules

Abstract: Recently we identified a molecular basis for differentiating benign and malignant follicular thyroid tumors. The purpose of these studies was to determine whether molecular analysis can be used to differentiate papillary thyroid carcinomas from benign thyroid nodules. Gene expression patterns of 14 papillary thyroid carcinomas and 21 benign tumors were analyzed by oligonucleotide array analysis. The carcinomas included seven classical papillary thyroid carcinomas (PTC) and seven follicular variant of PTC (FVPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 50 publications
9
90
3
3
Order By: Relevance
“…Such a failure could be explained by the great similarity in overall gene expression profiles observed between the 2 sample groups, as demonstrated by Figures 1 and 2, which may be further indication that the 2 lesions are similar not only phenotypically but also at the level of gene expression. Our data are in disagreement with those published previously by Finley et al and by Barden et al, [11][12][13] who identified a set of genes that, by clustering algorithms, could distinguish between adenomas and follicular carcinomas. This discrepancy may be explained by the number and identity of the genes present in our arrays compared with the arrays used by other groups or by differences in mathematical and statistical approaches.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Such a failure could be explained by the great similarity in overall gene expression profiles observed between the 2 sample groups, as demonstrated by Figures 1 and 2, which may be further indication that the 2 lesions are similar not only phenotypically but also at the level of gene expression. Our data are in disagreement with those published previously by Finley et al and by Barden et al, [11][12][13] who identified a set of genes that, by clustering algorithms, could distinguish between adenomas and follicular carcinomas. This discrepancy may be explained by the number and identity of the genes present in our arrays compared with the arrays used by other groups or by differences in mathematical and statistical approaches.…”
Section: Discussioncontrasting
confidence: 99%
“…Using oligonucleotide arrays, Finley et al identified differentially expressed genes among carcinomas, adenomas, and hyperplastic nodules; and the expression of those genes was used to cluster samples that represented different pathologies. 11,12 A similar technique was employed in the comparison of follicular carcinomas and adenomas and demonstrated different profiles after hierarchical clustering. 13 Recently, we described the identification of molecular classifiers that could distinguish between malignant and nonmalignant lesions of the gastric mucosa.…”
mentioning
confidence: 99%
“…We and others have previously shown that papillary thyroid carcinoma could be separated from benign nodules, ie follicular adenomas and hyperplastic nodules, by their mRNA expression profiles using cDNA microarray analysis. [42][43][44] By qRT-PCR evaluation, our preliminary data also showed that by using fresh-frozen materials, most cases of papillary carcinoma and follicular adenoma can also be separated by their expression of a small panel of several genes, namely CK19, CITED1, galectin 3, deiodinase 1, thyroglobulin, and pendrin. 45 However, these mRNA-based assays were found to be less reliable when applied to formalin-fixed, paraffin-embedded tissues, primarily due to the suboptimal RNA qualities in these specimens (unpublished data).…”
Section: Discussionmentioning
confidence: 66%
“…To date, a number of microarray studies have shown metallothioneins to be downregulated in thyroid carcinoma. 7,14,15 Huang et al 14 expanded on their initial microarray experiment by trying to identify novel tumour suppressor genes involved in thyroid carcinogenesis. They found that MT1G was downregulated in papillary thyroid carcinoma consequent to hypermethylation.…”
Section: Expression Patternsmentioning
confidence: 99%